Women in the Ancient Near East - Stol, Marten 1940-; Richardson, Helen; Richardson, Mervyn E. J. 1943- (Berlin Boston De Gruyter, 2016)
Women in the Ancient Near East offers a lucid account of the daily life of women in Mesopotamia from the third millennium BCE until the beginning of the Hellenistic period. The book systematically presents the lives of women emerging from the available cuneiform material and discusses modern scholarly opinion. Stol’s book is the first full-scale treatment of the history of women in the Ancient Near East.
Frontmatter -- -- Table of Contents -- -- Introduction -- -- Map -- -- 1. Her outward appearance -- -- 2. Marriage -- -- 3. The marriage gifts -- -- 4. The family -- -- 5. A second wife -- -- 6. Concubines -- -- 7. Marriage between equals -- -- 8. Marriage to a slave -- -- 9. Divorce -- -- 10. Adultery -- -- 11. Rape -- -- 12. Incest -- -- 13. The widow -- -- 14. Levirate marriage -- -- 15. Women’s rights of inheritance -- -- 16. Women-trafficking under the guise of adoption -- -- 17. Women robbed of their freedom -- -- 18. Women and work -- -- 19. The witch -- -- 20. Prostitution -- -- 21. Temple prostitution -- -- 22. Her physical life -- -- 23. The court and the harem before 1500 BC -- -- 24. The court and the harem after 1500 BC -- -- 25. Priestesses -- -- 26. Old Babylonian convents -- -- 27. Married holy women -- -- 28. Soothsaying -- -- 29. Women and worship -- -- 30. The Sacred Marriage -- -- 31. The Middle Assyrian law-book about women -- -- 32. The value placed on women -- -- Bibliography -- -- Indexes
Der Titel ist Teil des Projekts Knowledge Unlatched, Round2 Pre-Unlatch
Original edition: Vrouwen van Babylon. Prinsessen, priesteressen, prostituees in de bakermat van de cultuur. Uitgeverij Kok, Utrecht (2012).Translated by Helen and Mervyn Richardson
In English
Keywords: Civilization, Ancient; Sex role; Women; Altorientalistik; Frauen; Geschichte; Geschlecht; HISTORY / Ancient / General; Ancient Near Eastern Studies; Gender; History